Double and triple Lutz in artistic roller skating: Kinematic comparison - Fantozzi, S.; Di Michele, R.; Ciacci, S.; Giovanardi, A.; Merni, F. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Knowing the biomechanical key factors of each jump is fundamental for figure skating coaches in order to more effectively teach triple jumps to their athletes. Notwithstanding the number of studies on ice skating (King et al., 2004), no biomechanical jump analysis, to the knowledge of the present authors, was performed on roller skating. The purpose of the present study was to compare some kinematic characteristics of double and triple Lutz jumps in roller skating. Methods 5 elite male skaters performing a series of double and triple Lutz were acquired using 10 infrared cameras (Smart-D, BTS, Milan, Italy, 250 Hz). For the trunk, the upper limbs and the foot segments, markers were attached directly on specific anatomical landmarks. For the thigh and the shank segments, the calibrated anatomical system technique was exploited (Cappozzo et al., 1995). The resultant velocity angle was also considered. Five key events were identified for each jump: toe-pick (instant in which the toe-pick impacted the ground), end of gliding (last contact of the left foot), take-off (last contact of the right foot), maximum height (top of the flight phase), and landing (instant of contact with the ground). Results The hip and the knee were flexed at the toe-pick, whereas the flexion was clearly lower at the take-off. On the contrary, the ankle at toe-pick was in the neutral position, and plantarflexed at the take-off, but differently depending on the skater. The skaters` horizontal velocities at take-off for the triple Lutz (mean: 2.69 m/s) were lower than those for the double one (mean: 3.17 m/s). Vertical velocities at take-off showed slightly higher values for the triple (mean: 2.90 m/s) compared to the double (mean: 2.72 m/s) Lutz. The average resultant velocity angle in the 5 athletes was 40° in the double and 47° in the triple Lutz, at the take-off. The greatest difference between the double and triple jumps was the rotational velocity during the flight estimated from the rotation of the pelvis segment. The pelvis rotation velocity was higher in the triple Lutz already during the toe pick (means: 0.84 rev/s for double and 1.75 rev/s for triple one). Jumping height and flight time were higher for the triple jump for three skaters. Discussion For the first time a biomechanical comparison between the double and the triple Lutz in roller skating was performed. Some of these findings were already roughly known to coaches and skaters, but only in the present study some specific descriptors of the jump were characterized and quantified.